Physiological Responses and Yield of Wheat Plants in Zinc-Mediated Alleviation of Drought Stress - Ma, Dongyun; Sun, Dexiang; Wang, Chenyang; Ding, Huina; Qin, Haixia; Hou, Junfeng; Huang, Xin; Xie, Yingxin; Guo, Tiancai (Frontiers in Plant Science, 2017)
To evaluate the physiological responses of wheat to zinc (Zn) fertilizer application under drought stress, pot and field experiments were conducted on wheat plants grown under different soil moistures and treated with soil and foliar Zn applications. Photosynthetic characteristics, antioxidant content, Zn element concentration and the transcription level of genes involved in antioxidant biosynthesis were analyzed. Zn application increased SPAD and Fv/Fm of wheat flag leaves, while decreased lipid peroxidation levels and H2O2 content. Zn application increased the antioxidant content (ascorbate, reduced glutathione, total phenolic and total flavonoid) of wheat flag leaves, and enhanced the relative expression levels of two antioxidant enzyme genes, four ascorbate–glutathione cycle genes, and two flavonoid biosynthesis pathway genes under drought stress. Soil Zn application increased grain yield and Zn concentration by 10.5% and 15.8%, 22.6% and 9.7%, and 28.2% and 32.8% under adequate water supply, moderate drought, and severe drought, respectively. Furthermore, foliar application of Zn in the field increased grain yield and grain Zn concentration under both adequate water supply and rain-fed conditions. Zn plays a role in alleviating wheat plant drought stress by Zn-mediated increase in photosynthesis pigment and active oxygen scavenging substances, and reduction in lipid peroxidation. Furthermore, Zn fertilizer could regulate multiple antioxidant defense systems at the transcriptional level in response to drought.